2021
DOI: 10.1021/acs.jafc.1c02375
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Viscoelastic Solutions Based on Chiral Wormlike Micelles in Mixed Solutions Containing an Amphiphile Derived from Rosin

Abstract: A novel rosin-based photoresponsive anionic amphiphile, sodium N-azophenyl maleopimaric acid imide carboxylate (AzoMPCOONa), has been successfully synthesized. Its molecular structure was characterized by 1H and 13C NMR and mass spectrometry (MS). The photoisomerization of AzoMPCOONa was evaluated by ultraviolet (UV)–visible spectrometry and 1H NMR. The structure of AzoMPCOONa could be converted between the trans and cis isomers by irradiation with UV/visible light. Importantly, a fascinating photoresponsive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…When the concentration was 120 mmol·L –1 , R c reached 100 s –1 . The phenomenon could be attributed to the rosin rigid skeleton, which endowed the worm-like micelles with a high scission energy . The viscoelastic solutions showed wide linear viscoelastic regions at concentrations between 60 and 100 mmol·L –1 (Figure S10).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the concentration was 120 mmol·L –1 , R c reached 100 s –1 . The phenomenon could be attributed to the rosin rigid skeleton, which endowed the worm-like micelles with a high scission energy . The viscoelastic solutions showed wide linear viscoelastic regions at concentrations between 60 and 100 mmol·L –1 (Figure S10).…”
Section: Resultsmentioning
confidence: 98%
“…Due to the pressure from the dwindling petroleum resources, exploiting LMWGs from naturally occurring molecules or their derivatives as building blocks has drawn considerable attention. First, natural resources impart biocompatibility and biodegradability to supramolecular hydrogels, meeting the requirements for biomedical applications. , In addition, the naturally occurring molecules usually contain unique chiral structures, which may endow the microstructure with chirality. , In the past decades, supramolecular hydrogels prepared from cholic acid, amino acid, , carbohydrate, glycyrrhizic acid, ,, and so forth have been reported. Rosin as an abundant biomass resource has been widely used in inks, coatings, rubbers, adhesives, food products, and polyurethane materials. It is mainly composed of abietic acid, which contains an extremely hydrophobic rigid tricyclic hydrophenanthrene skeleton. Therefore, rosin is a promising candidate for preparing bio-based amphipathic LMWGs. What is more, the rigid structure contains multiple reaction sites, greatly simplifying complicated chemical synthesis. However, few reports have focused on rosin-based supramolecular hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…40 constructed a photoresponsive viscoelastic solution using a rosin-based amphiphilic surfactant; it exhibited gel properties and formed dextro-chiral worm-like micellar aggregates prior to UV irradiation, whereas under UV irradiation, the colloidal solution transformed into a slightly viscous solution, while the aggregates transformed into rod-like and spherical micelles. 41 Polymer self-assembly typically produces better stability and toughness than traditional surfactants, but the enhancement effect of rosin structure on the photoresponsive properties of azobenzene-contained amphiphilic polymers remains relatively poorly studied. Moreover, few investigators have studied the concrete influence of the azobenzene group's position on a given polymer's photoresponsive behavior assuming a similar structural composition and a similar hydrophilic: hydrophobic segment ratio.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some studies have suggested that changes in the molecular length and polarity of rosin-based azobenzene amphiphiles resulting from the cis–trans isomerization of azobenzene groups can be particularly obvious, imbuing rosin-based azobenzene amphiphiles with excellent photoresponsive self-assembly performance. Lei et al introduced a photoresponsive rosin-based surfactant (R-azo-Na) prepared using dehydroabietic acid; this surfactant foam quickly disintegrated when exposed to UV light, revealing its extraordinarily high photoresponsive efficiency . Zhai et al constructed a photoresponsive viscoelastic solution using a rosin-based amphiphilic surfactant; it exhibited gel properties and formed dextro-chiral worm-like micellar aggregates prior to UV irradiation, whereas under UV irradiation, the colloidal solution transformed into a slightly viscous solution, while the aggregates transformed into rod-like and spherical micelles . Polymer self-assembly typically produces better stability and toughness than traditional surfactants, but the enhancement effect of rosin structure on the photoresponsive properties of azobenzene-contained amphiphilic polymers remains relatively poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…17,22,23 The optimization of formulations is an effective way to prepare viscoelastic surfactant solutions with novel functionalities. Oppositely charged surfactants, 24,25 organic salts, 26,27 inorganic salts, 18,28 long-chain alcohols, 29 polymers, 30 and cyclodextrins 7,31 are additives that are widely used for this purpose. In addition, the improvement of surfactant structures has also been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%